Seed damaging field pests of cowpea (Vigna unguiculata) L.Walp.) in Benin: occurance and pest status - Dreyer, H.; Baumgaertner, J.U.; Tamo, Manuele (Informa UK Limited, 1994)
Three insect groups, known from the literature, were confirmed to make up a seed pest complex in cowpea fields in Benin Republic (West Africa). Several species of heteropteran pod‐sucking bugs (PSBs), two lepidopteran species, namely Maruca testulalis (Geyer) and Cydia ptyehora (Meyrick) and the weevil Apion varium Wagner occurred throughout southern Benin. Field infestations of PSBs and M. testulalis were always present, whereas A. varium and C. ptyehora occurrence was sporadic. Seed damage assessment at harvest time showed that in 80% of 25 fields, planted between 1990 and 1992, PSBs were the most important pests. PSB damage to seed usually ranged between 40 and 85%. Seed damage from M. testulalis was low, despite occasional high flower infestations. C. ptyehora was a minor pest in all locations. Significant correlations between seed damage and cumulative numbers of insect days (CD) during pod formation was found for all three groups. For PSBs alone, the CD values were significantly correlated with pod numbers. The results suggest that the PSBs are the most important cowpea seed pests in southern Benin, the main cowpea production area of the country. However, probable competition for seeds among pests may mask the true damage potential of any one of them. There is a need to study damage by the different pests during seed formation.